1986
DOI: 10.1111/j.1439-0442.1986.tb00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Methodik und Anwendung der Defaunierung beim wachsenden Wiederkäuer

Abstract: Methods and application of defaunation in the growing ruminantDefaunation (selective destruction of protozoa in the rumen) is suitable for the evaluation of the effects resulting from the activity of the rumen ciliate protozoa and also for possible growth promotion in ruminant fattening. In scientific experiments defaunation should be practised with detergents, whereas nutritive methods seem to be of advantage for the practical application of defaunation. Ruminants reared without ciliates from birth by isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 82 publications
2
7
0
1
Order By: Relevance
“…With HMS, also more butyric acid may have been produced from fermented starch than with LMS, because of the slight increase of rumen pH (Bannink et al, 2008). Alternatively, the increased proportion of butyric acid may reflect an increase in the number of protozoa at the highest level of maize starch as reported by Kreuzer (1986). Results of the fractional passage rates of Yblabelled forage agreed with those of Lund et al (2006).…”
Section: Rumen Fermentationsupporting
confidence: 82%
“…With HMS, also more butyric acid may have been produced from fermented starch than with LMS, because of the slight increase of rumen pH (Bannink et al, 2008). Alternatively, the increased proportion of butyric acid may reflect an increase in the number of protozoa at the highest level of maize starch as reported by Kreuzer (1986). Results of the fractional passage rates of Yblabelled forage agreed with those of Lund et al (2006).…”
Section: Rumen Fermentationsupporting
confidence: 82%
“…While rumen H2 S levels in Experiment 1 were adequate to maintain active fermentation, previous studies have shown that protozoa may also enable digestion to continue in sheep with less than 1 p H2S S/mL in the rumen (Hegarty et al 1991). This role of protozoa in maintaining rumen N and S supply has not previously been appreciated because most comparisons of faunated and fauna-free sheep have been made on S-and N-adequate diets which sustained rumen NH3 concentrations greater than 50 mgN/L (see Kreuzer 1986).…”
Section: Rumen Fermentationmentioning
confidence: 99%
“…without rumen protozoa). While differences in rumen N and S metabolism have been noted between faunated and fauna-free ruminants, these comparisons have usually been made when the diet provided sufficient N and S to meet the requirements of rumen microbes (Kreuzer 1986). Because the seasonal deficiencies of nitrogen (N) and/or sulfur (S) that occur in many Australian pastures may restrict rumen function (Kennedy and Siebert 1972; Rees et al 1982)) it was our concern that the productivity of fauna-free ruminants under these conditions could not be predicted from available information.…”
Section: Introductionmentioning
confidence: 99%
“…This improved productivity is associated with an increased protein flow from the rumen (VEIRA et aI., 1984;USHIDA et a\., 1986) and a greater protein to energy ratio in the nutrients available for absorption (BIRD, 1989). Protozoa release NH 3 as an end-product of protein digestion (MAlI and HUNGATE, 1965) so animals without protozoa usually have a reduced rumen NH 3 concentration (KREUZER, 1986). It has recently been suggested that sulphide production in the rumen may be similarly reduced when there are no protozoa in the rumen (IVAN et a\., 1986).…”
Section: Introductionmentioning
confidence: 98%